2013
DOI: 10.3109/02770903.2013.816725
|View full text |Cite
|
Sign up to set email alerts
|

Adiponectin attenuates human eosinophil adhesion and chemotaxis: implications in allergic inflammation

Abstract: These results indicate that adiponectin attenuates the eosinophil functions induced by eotaxin without affecting cell viability. The inhibitory effect was associated with diminished calcium signaling rather than altering of surface receptor expression. Increasing circulating adiponectin might be a novel therapeutic modality for treatment of asthma, especially in obese asthmatics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 43 publications
1
23
0
1
Order By: Relevance
“…Next, we needed to determine the mechanism underlying the APN‐driven chemotaxis during the osteogenesis of h‐JBMMSCs. APN has already been reported to activate the adenosine monophosphate‐activated protein kinase (AMPK) signalling pathway by binding with the membrane receptor AdipoR1 . In addition, the results from our present study confirmed that APN could promote the osteogenesis of h‐JBMMSCs through the APPL1‐p38 MAPK signalling pathway .…”
Section: Discussionsupporting
confidence: 86%
“…Next, we needed to determine the mechanism underlying the APN‐driven chemotaxis during the osteogenesis of h‐JBMMSCs. APN has already been reported to activate the adenosine monophosphate‐activated protein kinase (AMPK) signalling pathway by binding with the membrane receptor AdipoR1 . In addition, the results from our present study confirmed that APN could promote the osteogenesis of h‐JBMMSCs through the APPL1‐p38 MAPK signalling pathway .…”
Section: Discussionsupporting
confidence: 86%
“…52 The ability to induce migration of monocytes, macrophages and dendritic cells has been also documented in the case of chemerin. 53,54 In contrast, it has been reported that adiponectin inhibits eosinophil and endothelial cell chemotactic response, 55,56 whereas apelin suppresses chemotaxis of macrophages. 28 Therefore, activities mediated by adipokines seem to promote cell influx and their subsequent accumulation at the sites of ongoing inflammation.…”
Section: Adipokines Modulate the Activity Of Cells Engaged In Innatmentioning
confidence: 95%
“…In contrast to leptin, Yamamoto et al demonstrated that the adiponectin receptors AdipoR1 and AdipoR2 were expressed on human peripheral blood eosinophils but that adiponectin, in a dose-dependent manner, attenuated eotaxin-induced eosinophil adhesion activity 41. However, no effects were observed on the survival of eosinophils.…”
Section: Introductionmentioning
confidence: 99%